Using Powtoon Educational Videos to Enhance Interactive IPAS Learning - Oktoberiansyah; Siti Dewi Maharani; Syarifuddin (Journal for Lesson and Learning Studies, 2025)
Less interactive learning activities and teachers having difficulty developing interactive learning media have an impact on students' low mastery of concepts. This study aims to develop and implement educational video media based on Powtoon in learning the subject of Natural and Social Sciences (IPAS) for grade IV of elementary school with the aim of improving students' understanding of the material "Plant Body Parts". This study uses a research and development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects of the study were design experts, media experts, and language experts. The trial subjects were Thirty-One (31) grade IV students in elementary school. The methods used in collecting data were observations, interviews, questionnaires, and tests. The data collection instruments used questionnaire sheets and test questions. The techniques used to analyze the data were qualitative and quantitative, and an assessment of 4.83. Language validation with an assessment result of 4.44, which was included in the very valid category. The N-gain of 0.77 shows a high category, indicating that Powtoon-based animated learning videos can significantly improve student learning outcomes. It is concluded that Powtoon-based learning media is efficacious in improving the understanding and learning outcomes of grade IV students in elementary school. The implication of this research is that the Powtoon-based educational video media developed is suitable for use in learning.